Tamar, Lioness of Judah: A Modern Midrash in Her Own Voice - Feldman, Marla J. (Women in Judaism, 2024)
“Tamar, Lioness of Judah” is a modern midrash, based on Genesis 38:6-12, that weaves together elements from the classical midrash with contemporary feminist sensibilities in order to imagine how Tamar would tell her own story from her own perspective.